Efeito do tratamento local de vesiculite seminal sobre a qualidade e longevidade so sêmen equino - Silva, Yamê Fabres Robaina Sancler da [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Seminal vesiculitis has great relevance in reproductive clinic due to the difficulty of treatment, high rates of recurrence, risk of female contamination with pathogenic agents, retirement of animals and low fertility rates. Local treatment has been reported as the best therapeutic alternative, although no other studies have evaluated its effects on seminal quality and longevity. The aims of this study included: to investigate what are the main bacteria involved in the disease and the risk factors for stallions; to evaluate and to compare the effect of local treatment of seminal vesiculitis on the sperm kinetic parameters, morphology and viability (plasma membrane integrity), percentage of leukocytes and counting colony forming units (CFU) of fresh, cooled and frozen semen samples and the content of nitric oxide in the seminal plasma, before (M0) and after one week (M1) and one month (M2) therapy. The results allow us to infer that the seminal vesiculitis was more prevalent in adults and aged animals, the evolution of the disease appeared chronically in all selected animals, natural breeding was a risk factor for onset of the disorder, the bege coulor of semen and ejaculatory dysfunction were signs indicative of abnormalities in the gland and the most common bacteria involved in the pathogenesis of the infection was Pseudomonas aeruginosa. In general, the local treatment produced an improvement in semen quality after a week (M1) in fresh, cooled and frozen semen on the kinetic parameters and sperm viability (p<0.05). In fresh semen promoted reduction in the volume of ejaculate, sperm concentration increased, reducing the percentage of leukocytes and CFU/mL in M1 compared to the other moments (p<0.05). In frozen semen promoted reduction of lipid peroxidation and of ROS content in M1 compared to other moments (p<0.05). The cooled semen for 24 hours at 5°C and 15°C demonstrated similar efficiency in the pre and post-treatment ...

A vesiculite seminal possui grande relevância na clínica reprodutiva devido à dificuldade de tratamento, elevados índices de recidiva, risco de contaminação de fêmeas com agentes patogênicos, inutilização de animais e baixos índices de fertilidade. O tratamento local tem sido apontado por diversos autores como a melhor alternativa terapêutica, porém nenhum estudo avaliou seus efeitos na qualidade e longevidade seminal. Nesse sentido, os objetivos do presente estudo incluíram: investigar quais são as principais bactérias envolvidas na enfermidade e os principais fatores de risco para os garanhões; avaliar e comparar o efeito do tratamento local de vesiculite seminal quanto aos índices de cinética e morfologia espermática, integridade de membrana plasmática, porcentagem de leucócitos e contagem de unidades formadoras de colônias (UFC) de amostras seminais frescas, refrigeradas e congeladas e o teor de óxido nítrico no plasma seminal, antes (M0), após uma semana (M1) e um mês (M2) da terapia. Os resultados obtidos permitiram inferir que a vesiculite seminal foi mais prevalente em animais adultos e idosos, a evolução da enfermidade ocorreu de forma crônica em todos os animais selecionados, a monta natural constituiu um fator predisponente para o surgimento da doença, a coloração amarelada do sêmen e a dificuldade na ejaculação são sinais indicativos de alteração da glândula e a bactéria mais prevalente envolvida na etiopatogenia da infecção foi a Pseudomonas aeruginosa. De maneira geral, o tratamento local levou a uma melhora da qualidade seminal após uma semana (M1), no sêmen a fresco, refrigerado e congelado, quanto aos índices de cinética espermática e integridade de membrana plasmática (p<0,05). No sêmen a fresco promoveu redução do volume seminal, incremento da concentração espermática, redução da porcentagem de leucócitos e de UFC/mL no M1 em relação aos demais momentos ...
Keywords: Equino - Reprodução; Semen; Vesicula seminal Inflamação Tratamento; Bacterias - Pesquisa; Seminal vesicles